Oso en bicicleta = Bear on a bike - Blackstone, Stella; Harter, Debbie; Perez, Maria; Blackstone, Stella (Cambridge, MA : Barefoot Books, 2014)
Follows Bear as he rides a bicycle to the market, a wagon to the prairie, and even a carriage to a castle.
NP
Accelerated Reader
Text in English with parallel Spanish translation.
DMM02/18.
ESPANOL02/18.
Keywords: Transportation -- Juvenile fiction; Bears -- Juvenile fiction; Transporte -- Novela juvenil; Osos -- Novela juvenil; Spanish language materials -- Bilingual; Materiales en espanol, Bilingues; Stories in rhyme; Cuentos en rima